Language Engineering for Multi-Level Modeling (LE4MM): - Frank, Ulrich; Clark, Tony (Proceedings of the Research Projects Exhibition Papers. 35th International Conference on Advanced Information Systems Engineering (CAiSE 2023), 2023)
Abstract In this paper we present a long-term research project that started in 2011. Language Engineering for Multi-Level Modeling (LE4MM) combines research on fundamental challenges of conceptual modeling and software engineering with the design and implementation of a tool environment. This interplay between research and development has proved very fruitful. Notwithstanding, running a research project over a period of more than 10 years, especially when it involves software development, faces a number of specific challenges. While the main focus of the paper is on research questions and findings, we will also present lessons learned in the project
Keywords: language architecture; model-driven development; DSML; reuse; design conflict